(3TQM GdEQTGO aj Yde GdNdGa hGdLOds - (3TeS GdOjf CHh GdYHGS CMeO Hf Ndjd Hf SYGOI GdegdHi GdNhji GdTGaYjs; (3eMeO Hf eMeO GdYejOj,J (B615 (3g` s
(3ChdgG (B:s
(3GdMeO dhGMO EeJfY YOeg hGdTcQ dhGLH hLH s
(3BNQgG (B:s
(3Ch JYfi Hg JYdbg HEQGOGJ GdKhGH HGdEbJVGA HehLHg Ch JYfi Hg TF BNQ s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B69s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJhMjO hGdedd hGdfMds